2011
DOI: 10.1016/j.meatsci.2010.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grape seed extract on oxidative, color and sensory stability of a pre-cooked, frozen, re-heated beef sausage model system

Abstract: The processing of meats at the factory level can trigger the onset of lipid oxidation, which can lead to meat quality deterioration. Warmed over flavor is an off-flavor, which is associated with oxidative deterioration in meat. To avoid or delay the auto-oxidation process in meat products, synthetic and natural antioxidants have been successfully used.Grape (Vitis Vinifera) is of special interest due to its high content of phenolic compounds.Grape seed extract sold commercially as a dietary supplement, has the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 50 publications
5
49
0
3
Order By: Relevance
“…On the other hand, the GSE can be used as a natural food additive due to high antimicrobial and antioxidant activities (Hogan et al, 2001;Kulkarni et al, 2011;Lorenzo et al, 2013;Peng et al, 2010). Gokoglu and Yerlikaya (2008) also found that GSE had inhibition effect on the formation of melanosis of Parapenaeus longirostris stored at 4℃ for 3 days by sensory analysis and color measurements.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, the GSE can be used as a natural food additive due to high antimicrobial and antioxidant activities (Hogan et al, 2001;Kulkarni et al, 2011;Lorenzo et al, 2013;Peng et al, 2010). Gokoglu and Yerlikaya (2008) also found that GSE had inhibition effect on the formation of melanosis of Parapenaeus longirostris stored at 4℃ for 3 days by sensory analysis and color measurements.…”
Section: Introductionmentioning
confidence: 96%
“…[14][15][16] Grape seeds flour is gluten-free and can be included as a biologically active substance in foods consumed by people who suffer from coeliac. 17 The literature review provided the results for the antioxidant activity of grape seeds flour but the data published was not uniform.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there had been a growing interest in the use of byproducts rich in polyphenols emanating, from the winemaking industry, to produce extracts and novel products for the maintenance of human health (Kulkarni, De Santos, Kattamuri, Rossi, & Brewer, 2011;Perumalla & Hettiarachchy, 2011). As such, the extraction of polyphenols from waste material deriving from traditional industrial practices represents an attractive, sustainable and cost effective source of these high-value biological bioactives, which could be incorporated into foods.…”
Section: Introductionmentioning
confidence: 99%